Synthesis and Characterization of a Triphenyl‐Substituted Radical and an Unprecedented Formation of a Carbene‐Functionalized Quinodimethane. Issue 30 (24th March 2014) - Mondal, Kartik Chandra; Samuel, Prinson P.; Roesky, Herbert W.; Niepötter, Benedikt; Herbst‐Irmer, Regine; Stalke, Dietmar; Ehret, Fabian; Kaim, Wolfgang; Maity, Bholanath; Koley, Debasis
Abstract The trichlorosilylcarbene monoradical (CycAAC<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pght94768t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> .</alternatives>)SiCl3 (1) was directly converted to (CycAAC<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pght94766s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> .</alternatives>)SiPh3 (2) by substitution of the three chlorine atoms with phenyl groups without affecting the radical center adjacent to the silicon atom. In addition to the structure determination, compound 2 was studied by EPR spectroscopy and DFT calculations. The three hyperfine lines in the EPR spectrum of 2 are due to the coupling with 14N nucleus. Functionalized 1, 4‐quinodimethane Me2cAACC6H4CPh2 (7) was isolated, whereas carbon analogue of radical 2 was targeted. Cyclic voltammogram of 7 indicated that a stable radical‐anion 7<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pght9475x5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> .−</alternatives>, as well as a radical‐cation 7<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pght94760p" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> .+</alternatives>, can be prepared. Theoretical calculations showed that one‐electron ionization energy and electron affinity of 7 are 5.1 and 0.7 eV mol−1, respectively.